2015
DOI: 10.2320/matertrans.mbw201411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electron Beam Irradiation on Shear Strength of Laminated Sheet of Bio-Adaptable Polydimethylsiloxane (PDMS) and Polytetrafluoroethylene (PTFE) with Fracture Toughness

Abstract: Effects of homogeneous low voltage electron beam irradiation (HLEBI) without glue on the adhesive force of tensile shear strength (¸B) at each shear probability (P s ) of laminated PDMS/PTFE sheets of polydimethylsiloxane (PDMS) and Polytetrafluoroethylene (PTFE) were investigated. Although¸B of shear at low and mid P s of 0.06 and 0.50 were 0.015 and 0.04 MPa before treatment, 0.22 MGy-HLEBI enhanced the¸B up to the largest values of 0.098 and 0.11 MPa of the laminated sheets, respectively. They were more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…To break covalent bonds in PTFE molecules, ionizing rays, such as electron beams, can be used as many studies have shown that electron beam irradiation on PTFE at high temperature is an effective modification method through breaking the covalent bonds. [18][19][20][21] Oshima et al used electron beam irradiation to improve the radiation resistance of PTFE. 22 Ignat'eva et al studied the infrared spectra of PTFE before and after irradiation, and explained the mechanism of the PTFE crosslinking reaction, confirming that electron beam irradiation can break the covalent bonds of PTFE molecules.…”
Section: Introductionmentioning
confidence: 99%
“…To break covalent bonds in PTFE molecules, ionizing rays, such as electron beams, can be used as many studies have shown that electron beam irradiation on PTFE at high temperature is an effective modification method through breaking the covalent bonds. [18][19][20][21] Oshima et al used electron beam irradiation to improve the radiation resistance of PTFE. 22 Ignat'eva et al studied the infrared spectra of PTFE before and after irradiation, and explained the mechanism of the PTFE crosslinking reaction, confirming that electron beam irradiation can break the covalent bonds of PTFE molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, both adhesive bonding and adhesive-free adhesion between PDMS and other types of materials (resins such as PMMA, PP, and PE 2527 ; metals such as Cu, Fe, Pt, Au, and Al 27,28 ; and glass 2830 ) were also reported. However, these articles rarely reported on adhesion between PDMS and fluoropolymers, or the adhesion strength between PDMS and PTFE was too low for practical use 27,31,32 . In medical and food industries, adhesives are unlikely to be employ because they are regarded as contaminations.…”
Section: Introductionmentioning
confidence: 99%
“…The PE/PET laminated sheets were irradiated by using an electron-curtain processor (Type CB250/30/20 mA, Energy Science Inc., Woburn, MA, Iwasaki Electric Group Co. Ltd. Tokyo) 8,[11][12][13][14] prior to hot-press. The specimen was homogeneously irradiated with the sheet HLEBI with low energy through a titanium thin lm window attached to a 550 mm diameter vacuum chamber.…”
Section: Homogeneous Low Energy Electron Beam Irradiation (Hlebi)mentioning
confidence: 99%